Effects of infusion and steeping conditions on the total phenolic content of Centella asiatica using Folin-Ciocalteau method / Siti Nadirah Abdullah - Abdullah, Siti Nadirah (Faculty of Applied Sciences, 2009)
This study was carried out to determine the effects of infusion and steeping conditions on the total phenolic content of Centella asiatica (pegaga) using Folin- Ciocalteau method. The total phenolic content of Centella asiatica tea extract were investigated using two infusion techniques, by hot boiling water and hot water dispenser. Then each of infusion techniques was steeped in two different steeping time, five minutes and 15 minutes. The percent extraction yield of aqueous extract of Centella asiatica of the samples varied from 11.73 to 5.93. The highest percent extraction yield obtained in infusion of hot boiling water for 15 minutes (11.73) and the lowest percent extraction yield obtained in infusion of hot water dispenser for five minutes (5.93).The total phenolic content of the samples varied from 85.20 mg (GAE)/g. to 27.89 mg (GAE)/g, expressed in gallic acid equivalents (GAE). The aqueous extract of Centella asiatica using infusion in hot boiling water for 15 minutes exhibited the highest total phenolic content 85.20 mg (GAE)/g while the aqueous extract of Centella asiatica using infusion in hot water dispenser for five minutes exhibited the lowest total phenolic, 27.89 mg (GAE)/g. Hence, it can be concluded that the total phenolic content increased with higher temperatures and longer steeping times. This suggested that the customers can choose to prepare Centella asiatica tea using hot boiling water with 15 minutes because it can preserve higher amount antioxidant compound.